2010
DOI: 10.1021/cc100132z
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Highly Diverse Purine-Hydroxyquinolinone Bisheterocycles

Abstract: Solid-phase synthesis of bisheterocyclic compounds that contain purine and the 3-hydroxyquinolin-4(1H)-one skeleton connected with an aliphatic spacer of a different length/structure is described. The reaction sequence started from the primary amines immobilized on aminomethylated polystyrene resin equipped with an acid-labile linker (4-(4-formyl-3-methoxyphenoxy)butyric acid). After the arylation of amines with 2,6-dichloropurine via its C(6), purine N(9) was alkylated and subsequently the chlorine at purine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…In contrast, it is difficult to accomplish the subsequent substitution of the chlorine in the purine C 2 position. In the case of reactive nucleophiles (primary aliphatic amines, piperidines, or piperazines), the solid-phase amination can be accomplished using high boiling solvents, for example, DMSO, NMP, or diethylene glycol diethyl ether, at 150–200 °C. , To avoid these harsh conditions, an alternative approach was introduced by Brill who studied the possible C 2 substitution under Pd catalysis . He reported that the use of Pd 2 dba 3 as the promoter, P­( t -Bu) 3 as the coligand and K 3 PO 4 as a base furnished the desired products 48 in high yields (70–97%) at temperatures up to 100 °C.…”
Section: Immobilization Via the C6 Positionmentioning
confidence: 99%
“…In contrast, it is difficult to accomplish the subsequent substitution of the chlorine in the purine C 2 position. In the case of reactive nucleophiles (primary aliphatic amines, piperidines, or piperazines), the solid-phase amination can be accomplished using high boiling solvents, for example, DMSO, NMP, or diethylene glycol diethyl ether, at 150–200 °C. , To avoid these harsh conditions, an alternative approach was introduced by Brill who studied the possible C 2 substitution under Pd catalysis . He reported that the use of Pd 2 dba 3 as the promoter, P­( t -Bu) 3 as the coligand and K 3 PO 4 as a base furnished the desired products 48 in high yields (70–97%) at temperatures up to 100 °C.…”
Section: Immobilization Via the C6 Positionmentioning
confidence: 99%
“…A síntese orgânica em fase sólida (SOFS) [62][63][64][65] vem sendo uma alternativa viável na síntese de diferentes 3-carboxi-quinolin-4(1H)-onas. Srivastava et al, 66 preparam derivados da 3-carboxi-quinolin-4(1H)-ona a partir do tratamento da resina Merrifield (clorometilpoliestireno/divinilbenzeno) (41) com ácido 4-aminobenzóico (42) em presença de uma base (Cs 2 CO 3 ) para fornecer o intermediário (43).…”
Section: Síntese Em Fase Sólidaunclassified
“…Recently, a deeper attention has been paid to compounds bearing the carboxamide group located on a benzene ring of the quinolinone scaffold. For such compounds, a high-throughput solidphase synthesis concept has been developed [17][18][19] and targeted chemical libraries of 3HQs with the carboxamide group located in position 6, 7 and 8 were prepared. Both structurecytotoxicity 20,21 and structure-uorescence 22 relationships have been evaluated and derivatives with the most promising biological and uorescence properties were identied (Fig.…”
Section: Introductionmentioning
confidence: 99%